2021
DOI: 10.3103/s1541308x2102014x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the 2H/1H Isotope Composition of the Water Environment on the Probability of Denaturation Bubble Formation in a DNA Molecule

Abstract: The role of single protium-deuterium exchanges in formation of open-state bubbles is investigated using mathematical modeling methods. It is shown that the probability for formation of bubbles with a certain length (12 to 27 nucleotides) depends on localization of the deuterium atom in the DNA molecule and may be appreciably different from the general probability for occurrence of open states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…All of the above-mentioned may be due to the fact that repulsive forces can arise between the strands of the double DNA of the helix, observed, for example, in the field of external electromagnetic waves. Moreover, at certain resonance frequencies, the repulsive forces acting on the strands of the double helix lead to the damage and rupture of the strands of the molecule, or in the case of their longitudinal propagation (action of external forces along the axis of the DNA helix), stretching and unwinding of the double helix may occur [13,22,23], which makes nitrogenous bases much more vulnerable to damage under the influence of various mutagenic factors. Taking into account the fact that the natural frequency of the torque of a gene depends on the length of the DNA helix that forms it and, therefore, this value is specific for different types of cells and their genes, the calculation of the indicators of the natural frequency of DNA oscillations, for example, in the oncogenes or genes of microorganisms, followed by the effect of an external electromagnetic field of the corresponding intensity, can lead to the suppression of the expression of genes of bacteria and oncoproteins, i.e., to a decrease in the multiplication of biopathogens, and a decrease of the growth of tumor cells [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…All of the above-mentioned may be due to the fact that repulsive forces can arise between the strands of the double DNA of the helix, observed, for example, in the field of external electromagnetic waves. Moreover, at certain resonance frequencies, the repulsive forces acting on the strands of the double helix lead to the damage and rupture of the strands of the molecule, or in the case of their longitudinal propagation (action of external forces along the axis of the DNA helix), stretching and unwinding of the double helix may occur [13,22,23], which makes nitrogenous bases much more vulnerable to damage under the influence of various mutagenic factors. Taking into account the fact that the natural frequency of the torque of a gene depends on the length of the DNA helix that forms it and, therefore, this value is specific for different types of cells and their genes, the calculation of the indicators of the natural frequency of DNA oscillations, for example, in the oncogenes or genes of microorganisms, followed by the effect of an external electromagnetic field of the corresponding intensity, can lead to the suppression of the expression of genes of bacteria and oncoproteins, i.e., to a decrease in the multiplication of biopathogens, and a decrease of the growth of tumor cells [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Its concentration in blood plasma is four times more than potassium, six times more than calcium, ten times more than magnesium, and much more than the content of essential macro- and microelements, such as fluorine, iron, iodine, copper, manganese, and cobalt. It is important to note that the deuterium content in the blood plasma of healthy animals is 3–6 ppm higher than the level of deuterium in drinking water [ 3 , 4 , 5 ]. Although the concentration of deuterium in an organism is much lower than that of protium and reflects the D/H ratio in natural nonorganic and organic compounds, a wide variety of morphological and physiological changes have been shown in cells enriched with deuterium, including changes in fundamental processes such as cell division or energy metabolism [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, based on the angular model, it was found that the presence of deuterium in the chain of nucleotides can cause, depending on the value of the hydrogen bondbreaking energy, both an increase and a decrease in the probability of the occurrence of open states [23]. Moreover, the isotopic composition of the media, causing primarily a single 2 H/ 1 H replacement, affects the size of denaturation bubbles and the probability of their formation [24]. The angular model of DNA [25,26] makes it possible to take into consideration a quite wide range of external influences, such as the viscosity of the medium, the isotopic composition, and external forces [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%